Characteristics of consultations outside the maternal ICU associated with ICU admission and “Near Miss” events in obstetric patients - Paredes Saravia, Lourdes Maria (2024)
Introduction. Consultations outside the Maternal Intensive Care Unit (ICU) enable early identification of critical complicationsin obstetric patients, preventing clinical deterioration. Objective. To identify the characteristics of non-ICU consultationsand their relationship with maternal Near Miss events and ICU admission. Methods. An observational, correlational,and retrospective study was conducted, including 768 patients assessed outside the ICU at the Instituto Nacional MaternoPerinatal (INMP) between January and December 2022. Sociodemographic and clinical variables were collected. Bivariateand multivariate analyses were performed to evaluate the association between organ dysfunctions and the outcomesof Near Miss events and ICU admission. Adjusted risk ratios (RR) with 95% confidence intervals (CI95%) were estimated.A p-value <0.05 was considered statistically significant. Results. A total of 54% of the patients experienced Near Missevents. The main causes were hypertensive disorders (46%) and hemorrhages (23%). Respiratory dysfunctions (adjustedOR: 6.36; CI95%: 3.96–10.23) and electrolyte imbalances (adjusted OR: 3.17; CI95%: 2.07–4.87) were significantly associatedwith ICU admission. Direct request for transfer to ICU showed the strongest association with this outcome (adjustedRR: 2.16; CI95%: 1.80–2.60; p<0.001). Conclusion. Extramural consultations conducted by the ICU play a crucial role inidentifying obstetric complications and detecting Near Miss events. Strengthening ICU referral criteria and early responseis key to optimizing care and reducing morbidity and mortality in critical obstetric care.